2016
DOI: 10.15294/jdm.v7i2.8199
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Entrepreneurial Orientation and Collaborative Networks on Creative Industries Performance

Abstract: <p>            Creative industries significantly contribute to Indonesia economic development. There are many problems faced especially in improving innovation capabilities and competitive advantages. This study proposes to examine the effect of collaborative networks and entrepreneurial orientation to innovation capabilities, competitivee advantage and performance. Some creative industries located at several cities in the Central Java Province. Sampling methods used in this study is purposive sampling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 34 publications
(84 reference statements)
3
10
0
Order By: Relevance
“…The higher the ability to create competitive advantage is, the higher creative industry performance. The result of this study reinforces the finding that competitive advantage can improve business performance (Russell & Millar, 2014;Mulyana, 2016). Correspondingly, this research findings competitive advantage can improve organizational performance (Lakhal, 2009;Russell & Millar, 2014).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The higher the ability to create competitive advantage is, the higher creative industry performance. The result of this study reinforces the finding that competitive advantage can improve business performance (Russell & Millar, 2014;Mulyana, 2016). Correspondingly, this research findings competitive advantage can improve organizational performance (Lakhal, 2009;Russell & Millar, 2014).…”
Section: Resultssupporting
confidence: 88%
“…Business performance is significantly influenced by the competitive advantages of a company (Russell & Millar, 2014;Mulyana, 2016) and competitive advantage significantly affects financial performance (Kamukama et al, 2011). Strong competitive advantage improves organizational performance (Lakhal, 2009;Russell & Millar, 2014;Putri & Yuniawan, 2016).…”
Section: Innovation and Competitive Advantagementioning
confidence: 99%
“…Besides product innovation, previous scholars have found that co-creation value has a positive influence on business performance, as shown by Hamidi and Gharneh [18] and Fonjong and Tian [21]. Similarly, Mulyana & Sutapa [22] demonstrate a positive influence of the collaborative network on firm performance. In their research, Shahbaz, et al [23] exhibit that out of three dimensions of supply-chain collaboration, only two dimensions, namely informational sharing and joint decision-making, positively affect operating performance.…”
Section: Introductionmentioning
confidence: 92%
“…Entrepreneurial orientation and competitive advantage play an important role in improving the performance of the firm. Entrepreneurial orientation is a key success factor of the organization, as some studies indicates a positive relationship between entrepreneurial orientation and business performance (Zhang & Zhang, 2012;Mahmood & Hanafi, 2013;Mulyana and Sutapa, 2016). Entrepreneurial orientation arises from systematic testing of the entrepreneurial aspects of strategic decision making in companies that exist (Edmond & Wiklund, 2010), and it becomes as a certain behavioral patterns that are believed to be important appear in a business (Covin and Slevin, 1991;Lumpkin and Dess, 1996).…”
Section: Literature Review and Conceptual Framework Developmentmentioning
confidence: 99%